Effect of twin boundary on the initial yield behavior of magnesium nanopillars under compression: molecular dynamics simulations. (14th February 2018) - Mei, Hai; Xu, Shuang; Liu, Lisheng; She, Wuchang; Li, Jun; Fu, Zhengyi
Abstract: Nanotwinned Mg nanopillars under uniaxial compression were investigated by molecular dynamics simulations. The simulation results indicate that more { 10 1 ̄ 1 } ⟨ 10 1 ̄ 2 ̄ ⟩ TBs and less { 10 1 ̄ 2 } ⟨ 10 1 ̄ 1 ̄ ⟩ TBs are recommended to introduce for obtaining Mg nanopillars being of higher compressive yield strength. The pre-built { 10 1 ̄ 1 } ⟨ 10 1 ̄ 2 ̄ ⟩ TBs restrains the nucleation of new twins, and subsequently causes the increase of the yield strength. The initial yield behavior of nanotwinned Mg nanopillars with { 10 1 ̄ 1 } ⟨ 10 1 ̄ 2 ̄ ⟩ TBs was found to be twinning nucleation, and the nucleation mechanism is a shuffling mechanism. The introduction of { 10 1 ̄ 2 } ⟨ 10 1 ̄ 1 ̄ ⟩ TBs bring sources of dislocations into Mg nanopillars and subsequently causes the decrease of yield strength.